A Manifesto for Posthuman Creativity Studies. (June 2022) - Harris, Daniel; Holman Jones, Stacy
This article advances a manifesto for a posthuman creativity studies that highlights the emergent, collective, and ecological aspects of creativity, offering propositions that problematize any individualist or human-exceptionalist approach to the field. We attend to a range of extra/ordinary affects, encounters, and modalities for expanding creative possibilities in the 21st century. Beginning with a recognition that creativity must be rewilded from its current capture in economic and educational discourses, we argue for more sustainable re-engagements. In the specificity of these encounters, we manifest 10 commitments to posthuman creativity as the foundations for a more dynamic and more-than-human creative agency.